Artificial intelligence for big data : complete guide to automating big data solutions using artificial intelligence techniques. - Deshpande, Anand (Packt Publishing, 2018)
Create smart systems to extract intelligent insights for decision making. You will learn about widely used Artificial Intelligence techniques for carrying out solutions in a production-ready environment. You'll explore advanced topics such as clustering, symbolic and sub-symbolic information representation, and many more.- Resumé vydavatel
Keywords: big data; umělá inteligence; artificial intelligence; monografie; elektronické knihy; monographs; electronic books